An Integrated Practical Evidence-Based Medicine Curriculum, Critical Appraisal: Harm/Causation and Prognosis - Rachel Boykan; Maribeth Chitkara (Association of American Medical Colleges, 2014)
Abstract Introduction The need to teach evidence-based medicine (EBM) goes beyond meeting the requirements of residency. For residents and all practicing physicians there must be a process to ensure that doctors know the latest and best information to apply to the care of their patients. Typically, in the majority of pediatric training programs, EBM is taught in the context of a journal club, which may not develop the skills needed to integrate EBM into one's own clinical practice. Rather than memorizing facts and creating ingrained habits, medical residents and students in training must learn to be flexible in their clinical approach, integrating best evidence as it becomes available. In this 1-hour session, residents are reintroduced to basic EBM principles and given instruction regarding the appraisal of articles about harm/causation and prognosis. Methods Guided practice both during and after the sessions reinforces skills learned. This small-group session is intended for use in a longitudinal EBM curriculum. The first five sessions, how to develop an answerable clinical question/utilize evidence-based resources, how to appraise an article about a diagnostic test, how to appraise a systematic review or meta-analysis article, and how to appraise an article about therapy have been described in separate MedEdPORTAL publications. Results Participants completing the first year of this longitudinal EBM curriculum were evaluated using a quiz comprised of true/false, matching, and multiple-choice questions prior to the initiation and at the completion of all small-group sessions. Evaluation of the first two cohorts of residents participating in our curriculum revealed overall improvement in EBM knowledge. These data have been presented at regional and national conferences, including the Association of Pediatric Program Directors and Council on Medical Student Education in Pediatrics meeting, April 2013, the Northeastern Group on Educational Affairs meeting, April 2013, and the Pediatric Academic Society Meeting EBM Special Interest Group, May 2013. Discussion The need to teach EBM goes beyond meeting the requirements of residency. In this session, learners are reintroduced to basic EBM principles and given instruction regarding the appraisal of articles about harm/causation and prognosis. Guided practice both during and after the sessions reinforces skills learned. While the curriculum was designed for and has been studied on pediatric residents, it could easily be adapted for use by a broader audience including residents of any specialty, and medical students in their last 2 years of medical school.